Komparasi Kelembagaan Coast Guard di Empat Negara: Analisis Praktik Baik Untuk Indonesian Coast Guard [Comparison of Coast Guard Institutions in Four Countries: Analysis of Good Practices For The Indonesian Coast Guard] - Bulandari, Desty (Jurnal Politica, 2025)
Maritime security is a critical element for countries with sea access, including Indonesia, which has vast and strategically important waters. However, Indonesia faces challenges due to overlapping authorities in maritime law enforcement, leading to inefficiencies in addressing threats such as illegal fishing, smuggling, and piracy. This study aims to compare the coast guard institutions in four countries: Australia, South Korea, People’s Republic of China (PRC), and Singapore, to identify good practices applicable to Indonesia. A comparative method is employed to examine the institutional structures to the functions of the coast guard in each of these countries. The findings reveal that each country adopts different approaches. Australia prioritizes a multi-agency approach with collaboration between civilian and military agencies, while South Korea emphasizes specific task allocation and clear coordination in law enforcement. PRC highlights the importance of integrating maritime law enforcement agencies under a unified command with strong political support and a robust legal framework. Singapore, on the other hand, applies a Whole-of-Government approach, where all institutions related to maritime security work together synergistically to maintain maritime security. Based on this analysis, it is recommended that Indonesia establish a clear institutional framework through legislation to enhance the effectiveness of maritime security governance. Abstrak Keamanan maritim merupakan elemen penting bagi negara-negara dengan akses laut, termasuk Indonesia, yang memiliki wilayah perairan luas dan strategis. Namun, Indonesia menghadapi tantangan akibat tumpang tindih kewenangan dalam penegakan hukum maritim, yang menyebabkan inefisiensi dalam menangani ancaman seperti penangkapan ikan ilegal, penyelundupan, dan pembajakan. Penelitian ini bertujuan untuk membandingkan kelembagaan coast guard di empat negara: Australia, Korea Selatan, Republik Rakyat Tiongkok (RRT), dan Singapura, guna mengidentifikasi praktik baik yang dapat diterapkan di Indonesia. Metode komparatif digunakan untuk menelaah struktur hingga fungsi coast guard di masing-masing negara tersebut. Hasil penelitian menunjukkan bahwa setiap negara memiliki pendekatan yang berbeda dalam pengelolaan coast guard mereka. Australia mengutamakan pendekatan multi-agensi dengan kolaborasi antara lembaga sipil dan militer, sementara Korea Selatan menekankan pembagian tugas yang spesifik dan koordinasi yang jelas dalam penegakan hukum. RRT menunjukkan pentingnya integrasi lembaga penegakan hukum maritim di bawah satu komando dengan dukungan politik yang kuat dan kerangka hukum yang kokoh. Singapura, di sisi lain, menerapkan pendekatan Whole-of-Government, di mana semua lembaga yang terkait dengan keamanan laut bekerja sama secara sinergis untuk Indonesia menetapkan kerangka kelembagaan yang jelas melalui peraturan perundang-undangan.